The role of prolonged progestin treatment and factors predicting successful fertility-sparing treatment for early endometrial endometrioid adenocarcinoma. (December 2021) - Ou, Yu-Che; Fu, Hung-Chun; Lan, Jui; Wu, Chen-Hsuan; Kung, Fu-Tsai; Lan, Kuo-Chung; Tsai, Yi-Chen; Lin, Hao
Abstract: Objective: Fertility-sparing progestin therapy is highly effective in selected young women with endometrial cancer. In present study, we attempted to evaluate the role of prolonged medication and identify factors predicting successful treatment, and also assess fertility outcomes among young women with early stage endometrial endometrioid carcinoma (EC). Study design: We retrospectively reviewed clinical data from patients aged <45 years with well-differentiated EC at presumed stage IA (without myometrial invasion) who wished to preserve fertility. They were managed with oral progestin at Kaohsiung Chang Gung Memorial Hospital between June 2005 and June 2019. Results: Forty-five patients were included with a median follow-up of 53.5 months (range 12–170 months). Forty-one patients (91.1%) had complete remission, the cumulative complete response (CR) rates at 3, 6, 9, 12, and >12 months were 17.7%, 48.9%, 60.0%, 68.9% and 91.1%, respectively. Among the 41 responders, 23 attempted to conceive and nine (39.1%) achieved pregnancy with 12 live newborn infants. Eleven (27.5%) responders experienced recurrence at a median of 22 months from CR (range 3–54 months). Multivariate Cox regression analysis revealed that non-diabetes (HR: 4.59; 95% CI: 1.62–12.98) and endometrial thickness <2 cm (HR: 0.39; 95% CI: 1.41–17.67) were significantly factors associated with treatment response. Conclusions: We concluded that prolonged oral progestin treatment was possible with a certain proportion of responders (24.4%) being responded after one year. Diabetes controlled on metformin and endometrial thickness <2 cm could be used as surrogate markers to predict better treatment response.